The Effects of Acorn Flour on Some Quality Characteristics of Chicken Patties - Eylem Ezgi Fadıloğlu; Haluk Ergezer (Turkish Journal of Agriculture: Food Science and Technology)
The study was carried out to develop chicken patties by incorporating acorn flour as a meat replacer at 3%, 6%, and 9% levels in the formulation. For this purpose, the chemical (moisture, protein, fat, ash), pH, thiobarbituric acid (TBA), and color analyses in the raw and cooked chicken patties were analyzed. In addition, the cooking properties (cooking yield, diameter reduction, thickness reduction), functional properties (moisture and fat retention) and sensory properties were examined on cooked chicken patties. There were significant changes in the chemical, cooking, functional, and color properties of chicken patties with acorn flour. The moisture and protein values decreased, in both raw and cooked samples incorporated with acorn flour but fat level increased only in raw acorn flour added samples. Lightness (L*) and redness (a*) values decreased significantly. The addition of acorn flour caused an increase in b* values of raw samples and a decrease in cooked samples.  Acorn flour was not effective in preventing lipid oxidation. The addition of acorn flour contents in chicken patties improved functional and cooking properties, decreased cooking loss, and increased moisture and fat retention. The use of acorn flour improved the quality parameters of patties, but the addition of acorn flour resulted in a darker color in patties.  The use of acorn flour in chicken meatballs did not negatively affect sensory properties except color. In conclusion, acorn flour can be used as a filler and binder in chicken patties.